Experimental and model analysis of the thermoelectric characteristics of serial arc in prismatic lithium‐ion batteries - Wenqiang Xu; Languang Lu; Kai Zhou; Yalun Li; Bin Gao (IET Energy Systems Integration)
Abstract Aiming at the electrical safety problems of lithium‐ion battery system due to series arc fault, a finite element simulation model of square battery under series arc fault is established based on the magnetohydro‐dynamic equations. The arc voltages at different electrode spacings are analysed, and the electric field distribution, magnetic field distribution, arc temperature and flow velocity around the arc are investigated to determine the maximum values and locations of the electric field strength, magnetic density, arc temperature and flow velocity at the time of the arc fault. Then, on the basis of the series arc experimental platform, determine the value of the arc starting voltage and the critical power supply voltage that produces a stable arc, analyse the evolution of the arc burning time with different loop currents, the evolution of the arc of the separation gap, and then summarise the effect of the disaster on the battery. Finally, the errors of simulation and experimental arc voltage and battery surface temperature are analysed to verify the accuracy of the model.